Musik sebagai Pemicu Interaksi: Etnografi Komunikasi tentang Dinamika Penyiar dan Pendengar Remaja di Pro 2 RRI Surabaya - Muhammad Dian Prasetiawan; Redi Panuju; Farida Farida (Social Science Academic, 2026)
This study examines the role of music as a trigger for interaction in the communication dynamics between broadcasters and teenage listeners of Pro 2 RRI Surabaya. The study is significant because, amid the rapid growth of digital media, radio continues to maintain audience engagement through a combination of music and participatory interaction. The objective of this research is to understand how music stimulates interaction and how communication dynamics are formed between broadcasters and teenage listeners. This study employs an ethnography of communication approach based on Dell Hymes’ theory to analyze communication events occurring within the context of radio broadcasting. A qualitative research method was used, with data collected through observation, in-depth interviews, and documentation involving broadcasters and listeners of Pro 2 RRI Surabaya. The findings reveal that music functions not only as entertainment but also as a communication medium that encourages listeners to participate through song requests, comments, and interactions across various digital platforms. The communication dynamics identified in this study are characterized by two-way, interactive, and participatory communication conducted through radio broadcasts as well as social media platforms such as WhatsApp, Instagram, and TikTok. The study concludes that music serves as a primary trigger for interaction while strengthening social relationships and emotional closeness between broadcasters and teenage listeners.